Prevalence of bovine tuberculosis in dairy cattle in China during 2010-2019: A systematic review and meta-analysis. - Qing-Long Gong; Yu Chen; Tian Tian; Xiaobo Wen; Dong Li; Yu-Hao Song; Qi Wang; Rui Du; Xiao-Xuan Zhang (Public Library of Science (PLoS), 2021)
Background Bovine tuberculosis (bTB), caused by members of the Mycobacterium tuberculosis complex bacteria, mainly Mycobacterium bovis (M. bovis), is a major threat to public health and economic development. There has been no systematic epidemiological assessment concerning bTB in dairy cattle in China. Methodology/principal findings Literature related to bTB in China was retrieved from China National Knowledge Infrastructure (CNKI), PubMed, ScienceDirect, VIP Chinese Journals Database, and Wan Fang Database to build the first meta-analysis for estimating the prevalence and infection moderators of bTB in dairy cattle in China. A total of 100 relevant studies published from 2010 to 2019 were included. We estimated the overall prevalence of bTB was 2.4% (95% CI: 2.1-2.8) during this decade. In the sampling year subgroup, the prevalence was lowest in 2017 or later at 0.8% (95% CI: 0.3-1.5). The lowest prevalence was 0.7% (95% CI: 0.5-1.0) in Northwestern China. The lowest prevalence was 2.1% (95% CI: 1.8-2.5) using SIT test. Heifer cows had the highest prevalence, which was 27.1% (95% CI: 9.7-49.2). The prevalence in scale farming was 3.7% (95% CI: 3.1-4.3), significantly higher than that in free-range farming (1.7%, 95% CI: 1.1-2.4). The prevalence of bTB was highest in summer at 4.0% (95% CI: 1.7-7.0). In addition, the influence of different geographical factors (altitude, longitude, latitude, precipitation, temperature, humidity) on the prevalence was analyzed. Conclusions/significance The results showed that bTB was widespread in China but has been gradually reduced through concerted national intervention. It is suggested that different countries should formulate corresponding prevention and control measures according to the epidemic situation in its cattle industry. Enhanced monitoring of warm and humid areas may play an important role in reducing the incidence of bTB. In addition, when large-scale breeding is promoted, attention should be paid to standardizing breeding management and improving animal welfare to reduce the prevalence of bTB in cattle.